Financial Performance of ICICI Bank and HDFC Bank – A Comparative Study: Examining the Financial Performance of ICICI Bank and HDFC Bank through Ratio Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Bank is very important for our country and our economy. Banks play an important role in the economic development of every nation. There are many types of bank like, Merchant bank, Co-operative bank, National bank, Private bank. Today the knowledge of banking system and its financial performance is very useful to Bank Customers, Companies, and Shareholders etc. Here compare to financial position of two banks ICICI bank and HDFC banks with financial tool of ratio and then take a decision that who get a strong financial position.